2014
DOI: 10.1159/000357975
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Growth Hormone Therapy: A Practical Approach

Abstract: Background: Early detection of suspected poor adherence to growth hormone (GH) therapy is crucial to achieve normal final height in GH-deficient (GHD) patients. Patients: 106 children (73 M, 33 F) with a median age of 10.47 ± 3.48 years (mean ± standard deviation score (SDS)) exhibited short stature (-1.76 ± 0.64 SDS) and a delayed bone age (8.68 ± 3.42 years). Severe GHD was found in 28, while partial GHD was seen in 78 cases, with low IGF-I values. Recombinant human GH was administered by daily subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Our findings concur with the wider rhGH literature, [10, 15, 24-26, 28, 29, 30, 33, 34, 36-38]. Factors unique to the wider literature included: fear of side effects/long-term complications [15, 27, 35], the preference [36] and convenience of an injection device (ease of use, technical handling, and storage) [10, 24, 36], and accessibility of the rhGH distributing pharmacy [15] as well as sociodemographic factors (more specifically, the level of parental school education) [24, 29, 34, 38].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings concur with the wider rhGH literature, [10, 15, 24-26, 28, 29, 30, 33, 34, 36-38]. Factors unique to the wider literature included: fear of side effects/long-term complications [15, 27, 35], the preference [36] and convenience of an injection device (ease of use, technical handling, and storage) [10, 24, 36], and accessibility of the rhGH distributing pharmacy [15] as well as sociodemographic factors (more specifically, the level of parental school education) [24, 29, 34, 38].…”
Section: Discussionsupporting
confidence: 93%
“…The full study selection process is illustrated in online supplementary Figure 1 (full reasons for exclusion are detailed in online suppl. Table 5 [10, 15, 24-30, 33-38]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bozzola et al suggested that regularly interviewing GHD patients could be a useful approach to improve adherence and also mentioned that communication with patients and their parents should be in a nonaggressive manner [66]. Muller et al conducted a randomized crossover study comparing a liquid formulation of GH with the older freeze-dried product and found that an overall preference was given to the liquid product, with 98% patients rating it as easier to use [67].…”
Section: Resultsmentioning
confidence: 99%
“…Carefully constructed healthcare plans are the key and should include educational programmes, home support and regular reinforcement. Furthermore, it is mandatory to regularly interview patients with a non-aggressive approach to ensure effective communication with patients and their parents [89].…”
Section: Adherence To Gh Therapymentioning
confidence: 99%